2021
DOI: 10.1113/jp281788
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of the gut microbiome impairs mouse skeletal muscle adaptation to exercise

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…PoWeR is an easy-to-deploy and effective combined training modality for inducing pronounced skeletal muscle adaptations in aged mice. Compared to young C57BL/6 mice, 23 , 24 , 32 old mice run less (10–12 km/night versus 6-8 km/night) on a wheel that is only weighted to 5 g (as opposed to 6 g). Nevertheless, fiber type transitions, muscle fiber hypertrophy, satellite cell proliferation, and myonuclear accretion were still similar in magnitude between young and aged.…”
Section: Discussionmentioning
confidence: 96%
“…PoWeR is an easy-to-deploy and effective combined training modality for inducing pronounced skeletal muscle adaptations in aged mice. Compared to young C57BL/6 mice, 23 , 24 , 32 old mice run less (10–12 km/night versus 6-8 km/night) on a wheel that is only weighted to 5 g (as opposed to 6 g). Nevertheless, fiber type transitions, muscle fiber hypertrophy, satellite cell proliferation, and myonuclear accretion were still similar in magnitude between young and aged.…”
Section: Discussionmentioning
confidence: 96%
“…35% of participants said they noticed an improvement in their muscle stiffness and recovery after sports while doing the study. As previously mentioned, a healthy gut microbiome has been shown to benefit many factors that are involved in sports performance and recovery [1][2][3]5,7,[41][42][43]. We also note that the same is true in reverse; exercise has been shown to strengthen the gut microbiome and increase biodiversity [4].…”
Section: Physical Resultsmentioning
confidence: 54%
“…Multiple studies have shown that a healthy, biodiverse gut microbiome is crucial for sports recovery and performance because it is thought to impact muscle growth [1,2], boost energy levels [3,4], strengthen bones [5], reduce inflammation [6], and improve sleep [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…15,31,32 Animal experimentations indicate a bidirectional communication between gut and skeletal muscle and point out that gut microbiota is critical for optimal muscle function. 34,35 In fact, the presence of an intact gut microbiome is necessary for normal muscle adaptations to exercise 36 and to promote adequate dietary protein digestion and amino acid absorption, a critical processes to counteract sarcopenia-associated muscle protein wasting. 37,38…”
Section: Effects Of Gut Microbiota On Skeletal Muscle and Aging-relat...mentioning
confidence: 99%